Carmen Luz Latorre y Akio Yonemura. Formation of urban low income class and education : Chile and Mexico. Tokio : Institute of Developing Economies, 1986. 225 p. (JRP Series ; no. 50) - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1987)
CARMEN LUZ LATORRE Y AKIO YONEMURA. Formation of Urban Low íncome Class and Education: Chile and México, JRP Series, núm. 50, Institute of Developing Economies, Tokio, 1986.